Organizational Change and Organizational Sustainability: The mediating effect of Innovative Human Capital - Saadi, I. A.; Che Razak, R (Opción, 2019)
The purpose of this paper is to empirically examine the relationships between organizational change and organizational sustainability with the mediating effect of innovative human capital among manufacturing SMEs in the Kurdistan Region of Iraq. A survey questionnaire distributed utilizing a self-administered method is undertaken among 506 SMEs’ senior executi- ves. Consequently, 312 sets of questionnaires were successfully collected and used for the analysis. The model was tested using Partial Least Squares (PLS) procedure. Results indicate that organizational change effect on orga- nizational sustainability. However, two out of three dimensions of organiza- tional change such as personal valence and principal support have no signi- ficant effect on organizational sustainability. The innovative human capital is found does not play a mediating role in the effect of organizational change on organizational sustainability.